Comparison of coordination in crawl between elite swimmers and triathletes - Millet, G. P.; Chollet, D.; Chalies, S.; Chatard, J. C. (2000)
To evaluate the coordination of arm stroking in crawl between similar level (national to elite) athletes with different swimming training, 19 triathletes (Tri) and 15 swimmers (Swi) performed 8 trials of 12.5 m at velocities corresponding to 80% to 100% of their maximal velocity (Vmax). Stroke phases (A: Entry and Catch; B: Pull; C: Push and D: Recovery), the index of coordination (IdC), stroke length (SL) and stroke rate (SR) were analysed on two arm strokes. IdC is the time (in % of the stroke duration) of common superposition of propulsive (IdC>0) or non-propulsive (IdC<0) phases between two arms (Chollet et al. 2000). With the swim velocity increase (from 80% to 100%Vmax), SL decreased (from 2.46 to 2.15 and from 2.09 to 1.70 m) and SR increased (from 36.2 to 51.2 and from 35.1 to 55.1 st.min-1) respectively for Swi and Tri. At every velocity, SL was higher for Swi than for Tri (p<0.0001). Swi IdC increased from -8.6 to 2.6 between 80% and 100%Vmax, since Tri IdC increased from -8.8 to 2.6 between 80% and 97%Vmax before decreasing (0.9) at 100%. Stroke phases were similar between Swi and Tri, except B was longer (p<0.05) for Tri between 84% and 97%Vmax; and, above 97%Vmax, C was longer (p<0.05) and D was shorter (p<0.01) for Swi than for Tri. Our results show a similar coordination between Tri and Swi. It emphasises the needs for Tri to improve their propelling efficiency, assessed by SL (Toussaint 1990) and their sprint skills, crucial for group starts. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)